ভাষার অভিমুখ - (:unkn) unknown (Bangiya Sahitya Samsad, 2010)
ভাষার অভিমুখ | Bhashar Abhimukh has a collection of essays written in and about Bengali language.
Bhashar Abhimukh
Keywords: Bengali; History of Literature; Bengali